2004
DOI: 10.4049/jimmunol.173.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin and TNF Produced by B Cells Are Dispensable for Maintenance of the Follicle-Associated Epithelium but Are Required for Development of Lymphoid Follicles in the Peyer’s Patches

Abstract: Organogenesis of Peyer‘s patches (PP), follicle-associated epithelium, and M cells is impaired in mice lacking B cells. At the same time, lymphotoxin (LT) and TNF are known to be critical for the development of PP. To directly address the function of LT and TNF expressed by B cells in the maintenance of PP structure, we studied the de novo formation of PP in B cell-deficient mice after the transfer of bone marrow from mice with targeted mutations in LT, TNF, or their combinations. We found that although the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…M cells in the PP have been implicated in the mechanism of murine listeriosis [32], although this issue remains controversial [33]. Since conventional TNF-KO mice develop normal M cells in their PP [30] while TNF D/D mice lack PP altogether, our results clearly establish that PP in TNF -/-mice per se play no obligatory role in pathogenesis or protection of mice from intestinal Listeria infection.…”
Section: Since Tnfsupporting
confidence: 52%
See 1 more Smart Citation
“…M cells in the PP have been implicated in the mechanism of murine listeriosis [32], although this issue remains controversial [33]. Since conventional TNF-KO mice develop normal M cells in their PP [30] while TNF D/D mice lack PP altogether, our results clearly establish that PP in TNF -/-mice per se play no obligatory role in pathogenesis or protection of mice from intestinal Listeria infection.…”
Section: Since Tnfsupporting
confidence: 52%
“…4). Nevertheless, PP in TNF -/-mice showed normal development of follicle-associated epithelium and normal distribution of M cells, suggesting that these PP are at least partially functional [29,30].…”
Section: Since Tnfmentioning
confidence: 99%
“…In contrast to MLNs, the organization of PPs was predominantly regulated by B cell-derived TNF (supplemental Figure 6), consistent with a previous study. 29 PP from B-TNF KO mice lacked FDCs and organized B-cell follicles (supplemental Figure 6). TNF produced by T cells did not play any appreciable role in organization of PPs since T-TNF KO mice displayed normal PP microarchitecture (supplemental Figure 6), and T,B-TNF KO mice did not show additional defects in PP structure, compared with B-TNF KO mice (supplemental Figure 6).…”
Section: Organization Of Lns Is Dependent On Cooperation Between Tnf-mentioning
confidence: 99%
“…[4][5][6][7] Accumulating evidence has indicated that the interactive processes involving chemokines and cytokines of the tumor necrosis factor superfamily (lymphotoxins/tumor necrosis factor [TNF]) play a critical role in the orientation of the splenic microarchitecture, such as compartmentalization of T and B cells, formation of marginal zone (MZ), and development of reticular morphology known as the FDC network in secondary lymphoid organs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Ablation of such signals in adult animals leads to the reduction, although not the complete eradication, of immune response characterized by reduced isotype switching, delayed affinity maturation, and compromised B-cell memory. 22 Therefore, the proper formation of microarchitecture within secondary lymphoid organs, including the FDC network, is essential for efficient and/or rapid immune response.…”
Section: Introductionmentioning
confidence: 99%